2009
DOI: 10.3945/ajcn.2009.27694
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bite size and oral processing time of a semisolid food on satiation

Abstract: This study shows that greater oral sensory exposure to a product, by eating with small bite sizes rather than with large bite sizes and increasing OPT, significantly decreases food intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
173
4
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 212 publications
(191 citation statements)
references
References 27 publications
13
173
4
1
Order By: Relevance
“…Whether these same patterns occur in children requires further investigation. Moreover, a larger bite size has also been identified as an element of eating microstructure which underpins faster eating rates and supports energy [17][18][19][20] and children [21]. The current evidence suggests that certain features of eating microstructure may promote faster eating rates during the meal, which may support increased energy intakes and over time may lead to weight gain.…”
Section: Introductionmentioning
confidence: 87%
“…Whether these same patterns occur in children requires further investigation. Moreover, a larger bite size has also been identified as an element of eating microstructure which underpins faster eating rates and supports energy [17][18][19][20] and children [21]. The current evidence suggests that certain features of eating microstructure may promote faster eating rates during the meal, which may support increased energy intakes and over time may lead to weight gain.…”
Section: Introductionmentioning
confidence: 87%
“…Eating fast has been associated with excess energy intake and overweight [7][8][9][10][11][12], while eating slowly is hypothesized to discourage excess energy intake by allowing time for peripheral satiation signals to be consciously recognized before overeating occurs. Recent experimental trials support a relationship between eating rate and energy intake during a single ad libitum meal [13][14][15], providing empirical evidence that eating behavior can mediate satiation (i.e., the processes during a meal acting to terminate eating) [16] thereby altering energy intake.…”
Section: Introductionmentioning
confidence: 99%
“…3). In a subsequent study, it was shown that changing the oro-sensory exposure of chocolate custard from 3 to 9 s/bite led to a 10 % lower ad libitum intake (43) . The suppressive effect of oro-sensory exposure time on ad libitum intake was confirmed in another study with orangeade, where we held the eating rate constant (150 g/min) but only varied the relative duration of sensory exposure (long: 30 s/min of consumption; short 15 s/min of consumption) (44) .…”
Section: Sensory and Metabolic Signals Involved In Eating Behaviourmentioning
confidence: 99%